Theo-Anthropocentric Religious Moderation Education in an Indonesian Islamic Boarding School - Muslih Hidayat; Irja Putra Pratama; Eko Purnomo; Nurul Hidayah; Hamidah Mohamad (Yayasan Darusssalam Bengkulu, 2026)
This study examines the theo-anthropocentric approach as a model of religious moderation education at Askaril Ikhlas Blower Islamic Boarding School, Aceh, Indonesia. The study is grounded in the need to strengthen students’ moral character, religious commitment, tolerance, and social responsibility amid moral decline, social conflict, and the challenges of globalization and digital transformation. Using a qualitative descriptive approach, data were collected through semi-structured interviews, observation, and documentation involving foundation administrators, boarding school leaders, religious teachers, dormitory supervisors, and students. The findings reveal that religious moderation is internalized through learning activities, worship habituation, student coaching, exemplary behavior, social interaction, and daily boarding school culture. The theo-anthropocentric approach is reflected in three main dimensions: divine awareness, humanitarian values, and environmental responsibility. Divine values are developed through Qur’anic learning, prayer discipline, dhikr, and religious guidance; humanitarian values are strengthened through tolerance, cooperation, compassion, and social care; while environmental responsibility is practiced through cleanliness, water conservation, and care for nature. The study also identifies tazkiyatun nafs through takhalli, tahalli, and tajalli as a spiritual strategy for transforming religious moderation from a cognitive concept into moral and social practice. This study contributes a holistic framework for religious moderation education that integrates faith, humanity, social ethics, and ecological awareness within Islamic boarding school life.